Management in banking - Howe, Steve G. (Worcester: Northwick publishers, 1990)
The book provides a course of study for examination for bankers. It is designed to be easy to read and follow and describes and explains the various topics within the syllabus.
Includes index
rua 05/09/16
Loans
Keywords: Banking; Management; Bank management; Great Britain